Nanocelluloses from phormium (Phormium tenax) fibers - Di Giorgio, Luciana (2020)
This work aimed in preparing nanocelluloses from a unique source of cellulose, viz. phormium (Phormiun tenax) fibers, by different techniques; and evaluate their physicochemical and structural properties. It was possible to obtain cellulose nanofibrils with different sizes (diameter, length and aspect ratio), morphology, crystallinity and surface charge by mechanical disintegration of bleached and refined phormium fibers previously modified or not with enzymatic and oxidative treatments with endoglucanases and 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), respectively. But it was not possible to prepare nanocrystals by acid hydrolysis, even when trying to modify the reaction conditions, possibly due at least partially to the presence of residual hemicelluloses and lignin. Process efficiency seemed to depend variably on the initial state of phormium (Phormiun tenax) fibers and the presence of other components such as lignin and hemicelluloses. These nanofibers could be used for different purposes in different areas according to their physicochemical characteristics.